Prevalence and Molecular Identification of Demodex folliculorum in Khuzestan Province, Iran: Associations with Demographic, Lifestyle and Clinical Factors - Gafar Jalali; Hamid Kassiri; Saber Gholizadeh; Mehdi Badakhshan (Journal of Arthropod-Borne Diseases, 2026)
Background: Demodex folliculorum (Acariformes: Demodicidae) is a common human ectoparasite associated with various inflammatory skin and ocular disorders. This study investigated the prevalence, associated factors and molecu-lar characteristics of D. folliculorum among individuals attending primary healthcare centers in Khuzestan Province, southwestern Iran. Methods: In this cross-sectional study, 228 participants underwent cutaneous and ocular sampling for Demodex detection using a light microscope. Selected positive samples were identified molecularly by 18S rDNA sequencing. Demographic, behavioral and clinical data were collected using standardized questionnaires. Variables associated with infestation were evaluated by univariate analyses and multivariable binary logistic regression. Results: Cutaneous Demodex infestation was detected in 20 participants (8.77%), while ocular infestation was identified in three participants. Molecular analysis confirmed all sequenced isolates as D. folliculorum, showing >99% similarity with reference sequences and only minor genetic polymorphisms. Multivariable analysis identified high psychological stress (adjusted odds ratio [AOR]=5.51, 95% confidence interval [CI]: 1.84–16.47; p=0.002) and active facial skin lesions (AOR=4.01, 95% CI: 1.22–13.20; p=0.022) as independent predictors of infestation. Ocular findings were reported descriptively because of the limited number of positive cases. Conclusions: Demodex folliculorum infestation was relatively uncommon in this population but was independently associated with psychological stress and active facial skin lesions. Molecular findings demonstrated close genetic similarity between local and globally reported isolates. These results improve understanding of the epidemiology of demodicosis and support molecular identification in epidemiological investigations